New Horizon of Plasmonics and Metamaterials - Kimata, Masafumi; Ogawa, Shinpei (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Plasmonics and metamaterials are growing fields that consistently produce new technologies for controlling electromagnetic waves. Many important advances in both fundamental knowledge and practical applications have been achieved in conjunction with a wide range of materials, structures and wavelengths, from the ultraviolet to the microwave regions of the spectrum. In addition to this remarkable progress across many different fields, much of this research shares many of the same underlying principles, and therefore, significant synergy is expected. This Special Issue introduces the recent advances in plasmonics and metamaterials and discusses various applications, while addressing a wide range of topics, in order to explore the new horizons emerging for such research.